SUPPLY CHAIN MANAJEMEN KOPI ORGANIK SERTA POTENSI PENGGORGANISASIAN BAGI PRODUSEN KECIL DI KAWASAN PARIWISATA UTARA LOMBOK TENGAH - Rengganis, Baiq Santi; Nirmawati, Nirmawati (AGRIBIOS, 2025)
The aim of this research is to understand the various value chains that exist in the coffee business in and around the Central Lombok Tourism Area, especially in the northern part. Furthermore, this research also aims to determine the feasibility of organizing small farmers in organic coffee production groups in the tourism area and to determine the performance of coffee supply chain management. Analysis of market demand in the Northern Tourism Area of ​​Central Lombok in terms of the last two years obtained using secondary data from related institutions and primary data obtained from coffee producers in the tourism area. To find out the spread of the coffee business, semi-structured interviews were conducted at each coffee retailer. The function of each actor is carried out through structured interviews and observations. This research also relies on focus group discussions in each village with producers to understand market relationships and the difficulties faced. The research results show that the marketing chain ! considered more effective than channel II, then the actor who plays a very important role in the coffee supply chain is KWT Rinjani and supply chain management shows a figure of 25.88%, which means that the coffee classification is considered very good with an average SCMPI of 3.192.